Temperature dependence of the Seebeck coefficient of epitaxial β-Ga2O3 thin films - Johannes Boy; Martin Handwerg; Robin Ahrling; Rüdiger Mitdank; Günter Wagner; Zbigniew Galazka; Saskia F. Fischer (APL Materials, 2019)
The temperature dependence of the Seebeck coefficient of homoepitaxial metal organic vapor phase grown, silicon doped β-Ga2O3 thin films was measured relative to aluminum. For room temperature, we found the relative Seebeck coefficient of Sβ-Ga2O3-Al=(−300±20) µV/K. At high bath temperatures T > 240 K, the scattering is determined by electron-phonon-interaction. At lower bath temperatures between T = 100 K and T = 300 K, an increase in the magnitude of the Seebeck coefficient is explained in the frame of Stratton’s formula. The influence of different scattering mechanisms on the magnitude of the Seebeck coefficient is discussed and compared with Hall measurement results.